2021
DOI: 10.1002/mbo3.1183
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis and antimicrobial activity of two fermented milk kefir samples

Abstract: In recent years, the fermented milk product kefir has been intensively studied because of its health benefits. Here, we evaluated the microbial consortia of two kefir samples, from Escarcega, Campeche, and Campeche (México). We considered a functional comparison between both samples, including fungal and bacterial inhibition; second, we applied shotgun metagenomics to assess the structure and functional diversity of the communities of microorganisms. These two samples exhibited antagonisms against bacterial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…The bacteria present in Ke r are responsible for the fermentative process that produces biomolecules with healthy bene ces. Studies have shown the effects of ke r against pathogenic bacteria, oxidative stress, in ammation, obesity, diabetes, osteoporosis, cardiovascular disease, and neurodegeneration [34]- [39]. Our previous works show that our sample of Brazilian ke r may contain metabolites and peptides with anti-Alzheimer's effects.…”
Section: Discussionmentioning
confidence: 74%
“…The bacteria present in Ke r are responsible for the fermentative process that produces biomolecules with healthy bene ces. Studies have shown the effects of ke r against pathogenic bacteria, oxidative stress, in ammation, obesity, diabetes, osteoporosis, cardiovascular disease, and neurodegeneration [34]- [39]. Our previous works show that our sample of Brazilian ke r may contain metabolites and peptides with anti-Alzheimer's effects.…”
Section: Discussionmentioning
confidence: 74%
“…For example, Tenorio‐Salgado et al. (2021) reported that bacteria species of two Mexican milk kefirs consisted of Acetobacter okinawensis (10.9%), L. kefiranofaciens (7.8%), and L. helveticus (2.8%) among others.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, a metagenomic approach was carried out to observe prophage signatures in bacterial metagenomes throughout the cider fermentation process. A total of 1174 putative prophage contigs were identified in silico in the bacterial metagenomes using VIBRANT software, such as has been done in cheese [44] and kefir [45]. Among them, two complete prophages were found, NODE_55 and NODE_129, matching with phages isolated from human gut metagenomic data.…”
Section: Discussionmentioning
confidence: 99%